The use of graphic design to brand musicking: a case study - Cameron, Lindi (Vaal University of Technology, 2019)
The way in which people consume music has changed over recent times, and the relationship between music and graphic design, once dominated by the ubiquitous album cover, has evolved. Along with cover art, musicians make use of branding, marketing, and promotion for all aspects of their published image, music performances, and products. The graphic designer working with musicians has had to adapt artwork to new formats, and build entire branding systems, which are prevalent in pop music, but seemingly less overtly utilised in classical music, which the study concentrates on. Due to waning attendance at live classical music concerts and increased streaming activity, both in audio and video, an opportunity exists within classical music, the focus of this study, to develop new audiences and nurture existing ones. The many tangential points that exist for graphic designers to consider in the music industry can be described as musicking, which pertains to all activities, processes, products and people involved in music-making, listening, recording, performing, producing and so forth, as explained by Elliott (1995) and Small (1999). This theoretical framework provides a lens for the graphic designer to view the totality and elements of the music industry and reconsider opportunities for collaboration and involvement. The goal of this study was to explore how one can use the principles and dynamics of graphic design to engage with and capture the dynamics of musicking in a branding project. In order to accomplish that, the main aim was to triangulate graphic design theory, musicking theory, and insights gleaned about and from a case-study client, to culminate in a practical case study using graphic design to support or capture the client’s musicking, so that the potential for refocusing the branding onto the musicking approach could be explored and interrogated. The literature revealed challenges and opportunities within the context of global consumption of music classical music and graphic design. The case study provided insights into a classical musician that records, teaches and performs, and his needs in terms of a practical project. The practical design project emanating from the exploration of musicking as an approach served as a culmination of insights gleaned from literature, the musician himself, and action research that may be transferable to designers working within the field of music branding, or musicians wishing to brand themselves. Findings showed that graphic design elements have the potential to echo the character of music, can act as a bridge to the artist and his or her stature, play an identifying and/or expressive role, and experientially transport listeners into meaningful engagement with the music. Recently, activities such as streaming have stripped music somewhat of the special, tactile context of physical packaging, but honouring audience expectations in a similar way in performance through graphic communication and artwork (including programs, screens, video and installations) offers other channels for reference points, as do online platforms for branding and engagement, that serve an interactive, dynamic interchange between artist and listener, promoting loyalty and support. As both the classical music industry and graphic design fields experience new demands brought about by technological advances, consumer behaviour and the vast options available to those digitally connected, great opportunity lies in the field of branding musicking. Classical music could potentially benefit from adopting a more audience-centric approach and consideration of a multisensory experience, as audiences have become spoiled for choice not only in music options available, but within the broader entertainment arena clamouring for their attention in a visually branded and captivating world. It simply is not enough anymore to believe that “[i]f you build it, he will come” (from the film Field of Dreams, in Parr 2015:4) and meaningful engagement with listeners through various touch points, builds lasting relationships and supportive fan bases that can ultimately affect a musician’s livelihood.
M. Tech. (Department of Visual Arts and Design: Graphic Design, Faculty of Human Sciences), Vaal University of Technology.
Keywords: Music branding; Musicking; Graphic design; Cover art; Performance graphics; Music visualisation; Piet Koornhof violinist; Classical musicking; Dissertations, Academic -- South Africa.; Graphic design (Typography).; Art music.; Branding (Marketing).; Performance art.